Relationship of Health Examination In Bus Driver with Traffic Accident Level in Sidoarjo District, 2019 - Umi Salkah (Journal of Public Health Science Research, 2020)
The increase in the number of traffic accident cases in Sidoarjo Regency in 2016 there were 1177 traffic accident cases, and an increase of 18.6% which in 2017 there were 1446 traffic accident cases. Whereas in 2018, there were 1518 cases of traffic accidents resulting in an increase of 4.74%. The purpose of this study was to analyze the relationship between health checks on bus drivers and the level of traffic accidents in Sidoarjo Regency in 2019 This study was an observational analytic study with a cross sectional study design with a total of 77 bus drivers in the Bungurasih Terminal. The results of the study based on the characteristics of the bus driver are the majority of male sex as many as 76 people (98.7%) and most are 41-50 years old as many as 34 people (44.2%). Based on statistical results the bus driver accident rate was influenced by variables of health examination results including blood pressure with Pvalue = 0,000, blood glucose variable with Pvalue = 0.023, while the results of respiratory alcohol and urine amphetamine tests on all bus drivers had negative results, so the value obtained constant and cannot be analyzed statistically. The conclusion of the study is the variable examination of pressure and examination of blood glucose while having a significant relationship with the level of traffic accidents in Sidoarjo Regency in 2019.